Seguimiento de labores agronómicas para el mejoramiento y calidad del cultivo de banano (Musa AAA simmonds) en la finca Santa Marta Fabio en Apartadó, Antioquia (2023)
The business practice was carried out at Santa Marta farm belonging to the company GRUPO 20. S.A, located in the municipality of Apartadó, Zona Bananera de Urabá. The objective of the business practice was to develop activities focused on the fruit protection tasks carried out by the operators, following the internal procedures manual. The main problems that affected the physical appearance of the fruit were identified, and to solve this, the management of field work was taken into account and in this way the importance of evaluating the execution of these activities within the cultivation, contributed to the efficiency in the production process and the implementation of timely correction strategies that in turn allow obtaining a final product with the quality that is requested within the demands of the market. In this way, with the implementation of the monitoring and training strategies in the farms, it was possible to exceed 95% of the quality of the cultural work in the cultivation of bananas.